Strategies for the development of volcanic hazard maps in monogenetic volcanic fields: the example of La Palma (Canary Islands) - José M. Marrero; Alicia García; Manuel Berrocoso; Ángeles Llinares; Antonio Rodríguez-Losada; Ramón Ortiz (Journal of Applied Volcanology, 2019)
Abstract Traditionally volcanic-hazard assessments have been applied to stratovolcanoes, where volcanic hazard maps represent important tools for volcanic crisis management and land-use planning. In recent years, several improvements have been made for monogenetic volcanic fields focused on, among other things, the development of spatial models to deal with one of the main problems in these areas, namely the unknown vent location. However, volcanic hazard maps of monogenetic volcanic fields present some significant differences with respect to those developed for stratovolcanoes, including the fact that they commonly represent multiple eruptive processes spread over the possible vent opening area. Likewise, the scientific communication of the volcanic-hazard assessment and how this information is comprehended are critical issues in the development of mitigation strategies for monogenetic volcanic fields. In this research, we focused on developing volcanic hazard maps using simple numerical hazard models in combination with a random approach for vent location to cover the whole vent opening area. We added some spatial methods to better manage potentially affected areas. The maps were designed for use in a digital environment (Geographic Information System) by Civil Protection professionals in high-risk monogenetic volcanic fields on small oceanic islands. The methodology presented does not use susceptibility base maps for hazard assessment to avoid possible underestimation of low probability areas by Civil Protection. The methodology represents an attempt to respond to the most important questions of where, when and how a new eruption might take place in a monogenetic volcanic field. The example presented here was developed for La Palma (Canary Islands).